On the performance of Mach-Zehnder-Interferometer (MZI) optical modulator on silicon-on-insulator (SOI) - Razak H.A.; Haroon H.; Zain A.S.M.; Menon P.S.; Shaari S.; Mukhtar W.M. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by WOS/ Scopus